CuI‐Catalyzed Synthesis of Functionalized Terminal Allenes from 1‐Alkynes. Issue 15 (27th March 2013) - Luo, Hongwen; Ma, Shengming
Abstract: Relative to our original protocol that uses CuI (0.5 equiv.), paraformaldehyde (2.5 equiv.), and dicyclohexylamine (1.8 equiv.), a facile and efficient protocol for the gram‐scale synthesis of functionalized terminal allenes by using CuI (7.5–10 mol‐%), paraformaldehyde (1.6 equiv.), and diisopropylamine (1.4 equiv.) has been developed. This method accommodates different functional groups such as hydroxy or carbonyl, and it also performed well in the synthesis of allenylamides and 2, 3‐butadien‐1‐ol. Abstract : A practical reaction for the CuI‐catalyzed synthesis of terminal allenes from terminal alkynes, paraformaldehyde, and i Pr2 NH was developed.